Recognising Early Literacy Development : Assessing Children's Achievements. - Nutbrown, Cathy (SAGE Publications, 1997)
Recognising Early Literacy Development reviews and evaluates a large number of existing texts and assessment instruments, and some LEA baseline assessment documents. The author considers the theoretical, political and educational purposes of literacy assessment; and discusses assessment practices as found in an original survey of assessment practice in one LEA. She explores the need for a new approach to measurement for research, which is more attuned to assessment for teaching, and the importance of appropriate approaches to finding out what young children know about literacy. The book.